IMPLEMENTASI MODEL PEMBELAJARAN SNOWBALL THROWING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Faoziyah, Nina (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study aims to determine the difference in increasing students' mathematics problem-solving abilities that obtain Snowball Throwing learning and those who obtain Direct learning. The method that is used in research is the method of quasi-experiment with the population of the entire student class VII one of the SMP Negeri in the city of Bandung in the teachings of 2012/2013, while the sample has two classes of the population that are selected by the random class. Instruments used in the research is about the ability to solve problems of mathematics type of description. The test is used to identify students mistakes of how to measure of students in completing the issue. To determine the increasing of student’s ability to solve problems mathematically between classroom control and class experiment, it can be done by using the calculation of the gain. The gain test results in increasing the mathematics problem-solving ability of students in the experimental class are 0,55 and the control class is 0,44. The second classes were on the middle criteria. From  the research is obtained the conclusion that: the increasing of students ability to solve problems mathematically students who acquire learning by using learning Snowball Throwing is better than students who received teaching direct mathematics.